2000
DOI: 10.1007/s101470050006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral adjuvant therapy with Carmofur (HCFU) for distant metastasis of colorectal cancer

Abstract: Background. The effectiveness of adjuvant chemotherapy for colorectal cancers after curative resection has been reported recently; this study was performed to clarify the reasons of for this effectiveness, which have been unclear. Methods. Two joint prospective clinical randomized studies were performed. In the first study, of patients operated on between July 1, 1981 and June 30, 1983, at 41 Centers in the Tokai district, 172 patients with colorectal cancer were allocated to two groups. In the control group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
2
5
0
Order By: Relevance
“…The greatest factor affecting the prognosis of colon cancer is hepatic recurrence, whose control is considered to be the most important factor in improving the prognosis [17]. The results of the present study, which demonstrated control of hepatic recurrence, were consistent with the results obtained with HCFU by other various investigators [9,11,17], and the efficacy of HCFU in the prevention of hepatic recurrence was demonstrated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The greatest factor affecting the prognosis of colon cancer is hepatic recurrence, whose control is considered to be the most important factor in improving the prognosis [17]. The results of the present study, which demonstrated control of hepatic recurrence, were consistent with the results obtained with HCFU by other various investigators [9,11,17], and the efficacy of HCFU in the prevention of hepatic recurrence was demonstrated.…”
Section: Discussionsupporting
confidence: 93%
“…The greatest factor affecting the prognosis of colon cancer is hepatic recurrence, whose control is considered to be the most important factor in improving the prognosis [17]. The results of the present study, which demonstrated control of hepatic recurrence, were consistent with the results obtained with HCFU by other various investigators [9,11,17], and the efficacy of HCFU in the prevention of hepatic recurrence was demonstrated. In the stratification analysis of DFS using Dukes' classification, the results for the chemotherapy group were good, with statistical significance in Dukes' B and a tendency to significance in Dukes' C. Also, the chemotherapy group had significantly better RFI in Dukes' B and C. Not only Dukes' C patients but also those in Dukes' B were considered to have a high risk of postoperative hepatic recurrence, and combination chemotherapy incorporating HCFU was thought to have potent effectiveness against hepatic recurrence in these patients.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore expected the destruction of nanocapsules by NIR laser light to be useful for the controlled release of drugs at targeted locations. To test this hypothesis, we encapsulated carmofur, a pyrimidine analogue used as an antineoplastic agent 51 , into LM nanocapsules. Ultraviolet–visible–NIR spectra showed a characteristic peak from carmofur at ∼266 nm after encapsulation; this corresponded to a slight shift to the red compared to the original carmofur solution (peak at 259 nm), caused by interaction of the drug with the LM and lipid shell ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A study in TNBC found that a nanoparticle containing docetaxel and fingolimod could abrogate lymphopenia while still blocking progression [ 183 ]. Carmofur, a derivative of 5′ fluorouracil and an inhibitor of acid CDase, has been used as adjuvant therapy in colorectal cancer patients to prevent metastasis [ 184 ]. The drug, which is known to cross the BBB, has been used for years in Japan as maintenance therapy following standard of care but has not been subjected to FDA approval in the United States [ 185 ].…”
Section: Altering Sphingolipid Metabolism For Therapeutic Intervenmentioning
confidence: 99%